Association of maternal, obstetric, fetal, and neonatal mortality outcomes with Lady Health Worker coverage from a cross-sectional survey of >10,000 households in Gilgit-Baltistan, Pakistan. - Daniel S Farrar; Lisa G Pell; Yasin Muhammad; Sher Hafiz Khan; Zachary Tanner; Diego G Bassani; Imran Ahmed; Muhammad Karim; Falak Madhani; Shariq Paracha; Masood Ali Khan; Sajid B Soofi; et al. (Public Library of Science (PLoS), 2024)
Pakistan has among the highest rates of maternal, perinatal, and neonatal mortality globally. Many of these deaths are potentially preventable with low-cost, scalable interventions delivered through community-based health worker programs to the most remote communities. We conducted a cross-sectional survey of 10,264 households during the baseline phase of a cluster randomized controlled trial (cRCT) in Gilgit-Baltistan, Pakistan from June-August 2021. The survey was conducted through a stratified, two-stage sampling design with the objective of estimating the neonatal mortality rate (NMR) within the study catchment area, and informing implementation of the cRCT. Study outcomes were self-reported and included neonatal death, stillbirth, health facility delivery, maternal death, postpartum hemorrhage (PPH), and Lady Health Worker (LHW) coverage. Summary statistics (proportions and rates) were weighted according to the sampling design, and mixed-effects Poisson regression was conducted to explore the relationship between LHW coverage and maternal/newborn outcomes. We identified 7,600 women who gave birth in the past five years, among whom 13% reported experiencing PPH. The maternal mortality ratio was 225 maternal deaths per 100,000 live births (95% confidence interval [CI] 137-369). Among 12,376 total births, the stillbirth rate was 41.4 per 1,000 births (95% CI 36.8-46.7) and the perinatal mortality rate was 53.0 per 1,000 births (95% CI 47.6-59.0). Among 11,863 live births, NMR was 16.2 per 1,000 live births (95% CI 13.6-19.3) and 65% were delivered at a health facility. LHW home visits were associated with declines in PPH (risk ratio [RR] 0.89 per each additional visit, 95% CI 0.83-0.96) and late neonatal mortality (RR 0.80, 95% CI 0.67-0.97). Intracluster correlation coefficients were also estimated to inform the planning of future trials. The high rates of maternal, perinatal, and neonatal death in Gilgit-Baltistan continue to fall behind targets of the 2030 Sustainable Development Goals.